A descriptive study of facial acanthosis nigricans and its association with body mass index, waist circumference and insulin resistance using HOMA2 IR - Shyam Verma; Resham Vasani; Rajiv Joshi; Meghana Phiske; Pritesh Punjabi; Tushar Toprani (Wolters Kluwer Medknow Publications, 2016)
Introduction: The term facial acanthosis nigricans (FAN) lacks definition of precise clinical and histopathological features. We present a descriptive study of patients with FAN to define pigmentary patterns and estimate the prevalence of obesity and insulin resistance in these cases. Materials and Methods: It is a prospective study that included all patients with classical AN of the neck and/or other areas with facial acanthosis nigricans described as brown-to-black macular pigmentation with blurred ill-defined margins, found on the zygomatic and malar areas. The body mass index (BMI) and waist circumference (WC) of the included patients were used as parameters of obesity.Homeostatic Model of Assessment of Insulin Resistance (HOMA2 IR) was used as a parameter to evaluate insulin resistance. Histopathological features of the 6 skin biopsies that were possible were reviewed. Results: Among the 102 included individuals, the patterns of facial pigmentation seen in addition to the classic pattern involving zygomatic and malar areas were a hyperpigmented band on the forehead in 59.80%, periorbital darkening in 17.64%, perioral darkening in 12.74%, and generalized darkening in 9.8% of cases. 85.29% of the males and 100% of the females were found to be obese. Varying degrees of insulin resistance was noted in 82.34% of the individuals. Six biopsies available for evaluation showed changes such as mild epidermal hyperplasia with prominent basal melanin, however, without the typical papillomatosis seen in AN of the flexures. Conclusion: We document an increased prevalence of obesity and insulin resistance in patients presenting with FAN and its presentations in addition to the classical description. We propose that FAN can be considered a cutaneous marker of insulin resistance and that HOMA2 IR can serve as a parameter of insulin resistance in such cases.